EDUKASI PROGRAM AQUATIC EXERCISE DALAM MENGURANGI KELUHAN SERTA MENINGKATKAN KEMAMPUAN FUNGSIONAL PASIEN NYERI PINGGANG KRONIK - Arif Pristianto; Wijianto Wijianto; Taufik Eko Susilo; Adnan Faris Naufal; Farid Rahman; Yasyfi Addiningsih (LPPM Universitas Abdurrab, 2021)
Low back pain (LBP) is a pain syndrome that occurs in the lower back region and the causes are degeneration, inflammation, infection, and musculoskeletal trauma. More than 70% of individuals in industrialized countries experience low back pain in their lifetime, and occurs at the age of 35-55 years. In Indonesia, it is not known for certain the number of sufferers who experience low back pain. However, it is estimated that 7.6% - 37% of Indonesians experience low back pain. Chronic low back pain (CLBP) causes changes in muscle activation and body posture, so that the individual's functional movement in activities decreases. The use of Aquatic Exercise treatment has been proven effective to improve physical function in patients with low back pain. This community service aims to increase the knowledge of clinical educators or land supervisors regarding variations in aquatic exercise methods in dealing with chronic low back pain in patients. The material given to participants relates to aquatic exercise management procedures in increasing functional activity in patients with chronic low back pain. This includes the movements performed and the equipment used in the intervention. The results of this community service are increasing the level of understanding of clinical educators about the use of aquatic exercise in treating patients with chronic low back pain, and increasing the ability of clinical educators to provide aquatic exercise treatment.